Productive use of specialized vocabulary in L2 culinary studies - Mohd Nordin, Nur Rasyidah; Hamin Stapa, Siti (Opción, 2019)
Food writing is a subject within culinary studies. Many students undergoing the food writing course are not equipped with the vocabularies within the culinary arts. This study will analyze students’ productive use of specialized vocabulary in their writing through 100 written documents collected from 10 students undergoing the food writing course; whose first language is Bahasa Melayu and the second language is English. The results show that the students were able to apply the specialized term appropriately in their writing in terms of the context and collocations used, with the presence of a few grammatical mistakes.